BUILDING EFFECTIVE AND SUSTAINABLE CORPORATE CULTURE THROUGH CONTEMPORARY LEADERSHIP - Valerieva Danchova, Mariya (Europa del Este Unida, 2021)
The effective leadership of an organization is the key to building sustainable corporate culture. Contemporary leadership is a fundamental factor and a challenge before the management of each organization in gaining market positions, guaranteeing the success and prosperity of the company, but this complex aspect contains the element of the effective corporate culture. It helps to create the suitable conditions for stimulation of the initiative and development of the leadership creativity of the employees. Building and maintaining resultant corporate culture is a key element facilitating the reaching and maintaining of the leadership position and the competitiveness of the organization. The main goal of the present article is to establish the connection and interaction between the effective and sustainable corporate culture and the contemporary leadership. The main research methods used in the article are content-analysis, comparative method and intuitive and systematic approach.